Removal of Cadmium(II) from Water using Modified Citrus limettioides Peels: Thermodynamic and Isotherm Studies - Janaki, P.; Sudha, R.; Sribharathi, T.S.; Anitha, P.; Poornima, K.; Premkumar, P. (Asian Journal of Chemistry, 2019)
The adsorption performance of sulphuric acid treated low cost adsorbent synthesized by using Citrus limettioides peel as an effective raw material for the removal of cadmium(II) from water. The batch adsorption method was carried out to optimize some parameters like contact time, pH and adsorbent dose. The nonlinear isotherm equations were used to calculate the different isotherm constant of five isotherm models namely Freundlich, Langmuir, Dubinin-Radushkevich, Redlich-Peterson and Sips. The Langmuir monolayer adsorption capacity of chemically modified Citrus limettioides peel was found to be 287.60 mg g-1. The negative values of ΔGº and ΔHº showed that the adsorption process is spontaneous and exothermic.